Training Needs Assessment (TNA) of the Women and Children Protection Desk (WCPD) Investigators: Basis for a Proposed Enhancement Program - De Lana, Marites S. Reyes –; Tanigue, Yolanda; Villa, Elizabeth B. (Future Science / FSH-PH Publications, 2024)
The thrust of the PNP is the continuing development and well-being of women and children investigators. To this end, a training needs assessment was conducted. This assessment is considered hybrid because it includes self-care, particularly the psychosocial and mental health needs of the WCPD investigators in their training. This study used a quantitative and descriptive approach to gather and analyze data. The questionnaire, which consisted of a 4-point scale, was used to assess the training needs of the WCPD personnel of the NCRPO from the regional headquarters down to its 5 district offices (NPD et al., and QCPD). Notably, the result of the study shows that family and self-care, including psychosocial and mental health, are highly needed as they describe the development and maintenance of stable physical and mental health. Additionally, the data gathered affirm that training and personnel capability enhancement and management and administration of assignments are highly needed. Specifically, the areas such as deployment of policewomen in the WCPD, placement of female WCPD Chief and personnel, Staffing Pattern and provision of an adequate number of personnel, strengthening of WCPC in the management of human resources, streamlining and efficient system of processing of the request for reassignment and placement of personnel, including the policy on reassignment, Standardization of WCPD offices, localization of assignment of WCPD investigators and required years of stay in the WCPD, are the points to be considered and improved in order to achieve optimum performance of WCPD as an office/ unit. Thus, the study provides an enhancement program for the training needs of WCPC investigators.